The current landscape of Acute Care for Elders units in the United States. Issue 10 (6th June 2022) - Rogers, Stephanie E.; Flood, Kellie L.; Kuang, Qiao Yu; Harrison, James D.; Malone, Michael L.; Cremer, Julia; Palmer, Robert M.
Abstract: Background: The clinical benefits of Acute Care for Elders (ACE) units have been established for over 25 years. However, how widely disseminated ACE units are in the United States and the degree of fidelity to the key elements of this model of care are unknown. Our objective was to identify all existing ACE units in the United States and to obtain detailed information about variations in implementation. Methods: The strategy to identify current ACE units began with online searches and snowball sampling using contacts from professional societies and workgroups. Next, a request for information regarding the existence of ACE units was sent to the remaining US hospitals listed in a national hospital database. An online survey was sent to identified ACE unit contacts to capture information on implementation characteristics and the five key elements of ACE units. Results: There were 3692 hospitals in the database with responses from 2055 (56%) hospitals reporting the presence or absence of an ACE unit. We identified 68 hospitals (3.3%) with an existing or previous ACE unit. Of these 68 hospitals, 50 (74%) completed the survey and reported that 43 ACE units were currently open and 7 had been closed. Of the 43 currently open ACE units, most are affiliated with an academic hospital and there is variable implementation of each of the five key ACE elements (from 69% to 98%). Conclusions: Among the 50 hospitals to complete the survey, 43 current ACE units were identified, with variable fidelity to the key elements. Estimates of prevalence of ACE units and fidelity to key elements are limited by nonresponses to the national survey request by nearly half of hospitals. Abstract : See related Editorial by Jo Cleveland in this issue.